COMPARISON OF TRUWINIST INTERDIGITAL METHOD AND CONVENTIONAL IN LEARNING APPROPRIATE DRUG SELECTION AND PRESCRIBING FOR TYPE 2 DIABETES MELLITUS - Trully Deti Rose Sitorus; Kuswinarti Kuswinarti; Istriati Istriati (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Medical education in Indonesia has been using Problem Based Learning curriculum. Meanwhile, the patient management ability evaluation showed the lowest result among all evaluation in Ujian Kompentensi Mahasiswa Program Pendidikan Dokter (UKMPPD). Truwinis Interdigital Method (TIM) has been developed to improve student ability in choosing the appropriate drug and prescribing for Diabetes Mellitus type 2. The purpose of this research is to compare the effectiveness of TIM toward Conventional Method (CM).Methods: This research used cross-sectional design. The subject is 82 student who attend Clinical Skill Laboratory of Endocrine and Metabolism System of Faculty Medicine of Universitas Padjadjaran. The subject is divided into two groups, Group I: CM (control), Group II: TIM (Intervention). TIM consist of e-learning and audiovisual material. Parameters in this research were ability of choosing appropriate drugs test and Objective Skill Clinical Examination (OSCE). The data is analyzed statistically. Results: The data showed homogenousity in both groups (p>0,05). The average test score for CM group was 25,11 ± 10,84 and for TIM group was 80,06 ± 14,19. This was statistically significant (p < 0,0001). The average test score of OSCE for CM group was 39,63 11,73 and for TIM group was 62,74 ±14 ,07. This was also statistically significant (p<0,0001).Conclusion: Truwinist Interdigital Method is more effective than the Conventional Method in learning appropriate drugs selection and prescribing for type 2 Diabetes Mellitus.